Malaysia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper analyzes the use of capital controls and evolution of the capital control regime in Malaysia. The paper highlights that following a period of strong downward pressures on the ringgit, the Malaysian authorities introduced on September 1, 1998 a wide range of capital controls along with pegging the exchange rate at RM 3.8 vis-a-vis the U.S. dollar. The paper provides a brief review of Malaysia's approach to capital account liberalization prior to September 1998. It also reviews the circumstances surrounding the imposition of the controls in September 1998, and their impact.